2007
DOI: 10.1158/1078-0432.ccr-06-1900
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Hepatocellular Carcinoma by Detection of Aberrant Promoter Methylation in Serum DNA

Abstract: Purpose: Most hepatocellular carcinomas (HCC) are diagnosed at an advanced stage. Hypermethylation of CpG islands in promoter regions is now recognized as an important early event in carcinogenesis and detection of methylated DNA has been suggested as a potential biomarker for early detection of cancer. There are no studies on epigenetic changes in samples from HCC patients before diagnosis. We explored the possible diagnostic value of aberrant promoter hypermethylation of three tumor suppressor genes in serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
128
2
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 166 publications
(141 citation statements)
references
References 33 publications
8
128
2
3
Order By: Relevance
“…Moreover, Liu et al (2006) reported the frequency of p15 methylation in (58%) out of 50 HCC cases versus (50%) out of 50 pericancer tissues but they did not include normal controls in their comparison. In contrast to our results, Zhang et al (2007) reported that aberrant methylation was found in serum DNA 1 to 5 years before clinical HCC diagnosis; they reported P15 methylation in 22% out of 50 HCC cases. However, they reported that out of 50 control cases, none had methylation of p15 which is matched with our results (Zhang et al, 2007).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Moreover, Liu et al (2006) reported the frequency of p15 methylation in (58%) out of 50 HCC cases versus (50%) out of 50 pericancer tissues but they did not include normal controls in their comparison. In contrast to our results, Zhang et al (2007) reported that aberrant methylation was found in serum DNA 1 to 5 years before clinical HCC diagnosis; they reported P15 methylation in 22% out of 50 HCC cases. However, they reported that out of 50 control cases, none had methylation of p15 which is matched with our results (Zhang et al, 2007).…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our results, Zhang et al (2007) reported that aberrant methylation was found in serum DNA 1 to 5 years before clinical HCC diagnosis; they reported P15 methylation in 22% out of 50 HCC cases. However, they reported that out of 50 control cases, none had methylation of p15 which is matched with our results (Zhang et al, 2007). On the other hand, Iyer et al (2009) reported P15 methylation frequency in 14.2% HCC Egyptian patients in tissues and 10.7% for plasma.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Detection of methylated DNA has then been suggested as a potential biomarker for early detection of cancer. In this study, HCC tumor tissues demonstrated hypermethylation in RASSF1A gene (88.6%, 31/35) and sera (40%, 14/35), which is in concordance with the findings from other investigators (tissue 60-92.5%; serum 42.5-70%) [18][19][20][21][22][23]. Although the exact mechanism of how the tumor DNA enters systemic circulation is unclear, the present result can still suggest that RASSF1A methylation should be a potential marker of incipient malignancy in the human hepatocarcinogenesis since, like any ideal biomarker, it appears early in the course of disease and is detectable in biological samples that can be obtained noninvasively.…”
Section: Discussionsupporting
confidence: 92%
“…The hypermethylation of RASSF1A suggests new perspectives for the diagnosis of malignant tumor. The methylation of RASSF1A was detected in the serum DNA of HCC patients by Yeo et al [18] and Zhang et al [19], as well as in the tissue DNA of HCC by Zhang et al [20], Di Gioia et al [21], Tischoff et al [22], and Schagdarsurengin et al [23]. But different groups obtained different data for the detection of hypermethylation of RASSF1A in HCC.…”
Section: Introductionmentioning
confidence: 99%